Phosphorus loadings estlmation and eutropidcation status of sungal layang reservoir using vollenweider model - Shamsudin, Supiah (Faculty of Civil Engineering, Universiti Teknologi Malaysia, 1997)
The study dealt with Phosphorus loadings estimation and lake eutrophication status using Vollenweider Steady-State Empirical Model. The phosphorus loadings predicted by Vollenweider's Model indicated that Sungai Layang Reservoir is an eutrophic lake. The mean hydraulics residence time obtained was 0.86 year and phosphorus loadings estimated was about 2.02 tons/year. Alternative methods of controlling phosphorus loading is briefly discussed.